2017
DOI: 10.3389/fpls.2017.01391
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling to Identify Genes Involved in Mesosulfuron-Methyl Resistance in Alopecurus aequalis

Abstract: Non-target-site resistance (NTSR) to herbicides is a worldwide concern for weed control. However, as the dominant NTSR mechanism in weeds, metabolic resistance is not yet well-characterized at the genetic level. For this study, we have identified a shortawn foxtail (Alopecurus aequalis Sobol.) population displaying both TSR and NTSR to mesosulfuron-methyl and fenoxaprop-P-ethyl, yet the molecular basis for this NTSR remains unclear. To investigate the mechanisms of metabolic resistance, an RNA-Seq transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(139 citation statements)
references
References 85 publications
11
128
0
Order By: Relevance
“…ha −1 , and the remaining 20 plants were treated with water (herbicide solution = control). All herbicides were applied as described previously by using an air‐compressed, moving‐nozzle cabinet sprayer . Thereafter, all seedlings were returned to the greenhouse and grown for another 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…ha −1 , and the remaining 20 plants were treated with water (herbicide solution = control). All herbicides were applied as described previously by using an air‐compressed, moving‐nozzle cabinet sprayer . Thereafter, all seedlings were returned to the greenhouse and grown for another 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous RNA‐Seq study had identified 31 candidate genes that may have conferred mesosulfuron‐methyl resistance to A. aequalis , with eight of them annotated to the P450 family (see Supporting Information, Table S3 in File S1). Here, we compared the expression levels of these eight P450 genes between the R (AHTC‐06F1) and S (AHHN‐02) populations, by using real‐time quantitative reverse transcription polymerase chain reaction (qRT‐PCR), following the methods described in our prior study . Alopecurus aequalis seedlings at the three‐ to four‐leaf stage from each population were sprayed with herbicides, as outlined in Table S4 in File S1 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Gardin et al, reported five candidate genes putatively associated with NTSR in black‐grass ( Alopecurus myosuroides Huds.). In our previous study, TSR and NTSR were shown to co‐exist in a single resistant A. aequalis population, named AH‐18, for which 17 candidate genes were putatively involved in its NTSR to mesosulfuron‐methyl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general review of the literature (Tables and S1) reveals a wide array of RNA‐seq experimental set‐ups employed by weed researchers over the last few years . These initial set‐up decisions can drastically influence the number of transcripts that appear as significantly differentially expressed by the end of the analysis.…”
Section: Lessons From the Literaturementioning
confidence: 99%